2022
DOI: 10.1128/iai.00364-22
|View full text |Cite
|
Sign up to set email alerts
|

FtlA and FtlB Are Candidates for Inclusion in a Next-Generation Multiantigen Subunit Vaccine for Lyme Disease

Abstract: Lyme disease (LD) is a tick-transmitted bacterial infection caused by Borreliella burgdorferi and other closely related species collectively referred to as the LD spirochetes. The LD spirochetes encode an uncharacterized family of proteins originally designated p rotein f amily t welve (PF12).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…However, after covalent modification by a fatty acid at its N-terminal Cys residue, the protein can be targeted into the periplasmic side of the cytoplasmic membrane, the periplasmic side of the outer membrane, or the external side of the outer membrane [ 12 ]. To clarify the exact location of the PFam12 proteins, prior experimental evidence indicated that FtlE is most likely a periplasmic inner membrane-attached protein, while FtlA, FtlB and FtlCare surface-exposed lipoproteins [ 23 , 24 , 27 ]. Since the lipoprotein signal sequence region in spirochetes may exhibit comparatively high variability, the PFam12 member FtlD was not included in any of the previous studies for lipoprotein localization [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, after covalent modification by a fatty acid at its N-terminal Cys residue, the protein can be targeted into the periplasmic side of the cytoplasmic membrane, the periplasmic side of the outer membrane, or the external side of the outer membrane [ 12 ]. To clarify the exact location of the PFam12 proteins, prior experimental evidence indicated that FtlE is most likely a periplasmic inner membrane-attached protein, while FtlA, FtlB and FtlCare surface-exposed lipoproteins [ 23 , 24 , 27 ]. Since the lipoprotein signal sequence region in spirochetes may exhibit comparatively high variability, the PFam12 member FtlD was not included in any of the previous studies for lipoprotein localization [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the current study we focused on the paralogous gene family 12 (PFam12), which contains five members (BB0844, BBG01, BBH37, BBJ08, and BBK01) that do not demonstrate meaningful sequence identity with proteins from any other organism which would allow us to judge the functions of these proteins. It is known that PFam12 members are surface-exposed and highly immunogenic lipoproteins that are upregulated as the tick starts the blood meal [ 8 , 13 , 14 , 23 27 ]. In a recent article studying the antigenicity and immunogenicity of PFam12 members, it was suggested to rename the proteins as f amily t welve l ipoproteins (Ftl) FtlA (BBK01), FtlB (BBG01), FtlC (BBH37), and FtlD (BBJ08) [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation